Effect of partial replacement of protein supplement with silkworm (Bombyx mori L.) pupa meal on production performances in crossbred (HS × GH) grower pigs - BARMAN, KESHAB; BANIK, S; THOMAS, R; KUMAR, SUNIL; DAS, ANIL KUMAR; DUTTA, KARABEE; RAJKHOWA, SWARAJ (The Indian Journal of Animal Sciences, 2021)
Eighteen crossbred (HS × GH) castrated grower pigs (3 months old, body wt. ranged from 13 to 14 kg) were divided into three groups of six each in a randomized block design to investigate the partial replacement of conventional protein sources with silkworm pupae (Bombyx mori) meal on production performance. Three different diets were prepared for feeding of experimental animals. These were namely - T1: standard grower ration without silkworm pupa meal and designated as control diet, T2: standard grower ration supplemented with 1.5% silkworm pupa meal by replacing 2.5% protein supplements which include mixture of groundnut cake and soyabean meal and standard grower ration supplemented with 3% silkworm pupa meal by replacing 5% protein supplements. The pigs were fed on the experimental grower rations twice daily in the morning and evening. The average dry matter intake was found similar in T1, T2 and T3 groups. Digestibility coefficients (%) of dry matter, crude protein, ether extract and crude fiber was increased in silkworm pupa meal supplemented groups. Nitrogen balance (g/d) was found positive across all the groups and was increased in supplemented groups in comparison to control. The average body weight gain (g/day) was found higher in silkworm pupa supplemented groups. The cost (`/kg gain) was reduced in T2 and T3 groups in comparison to T1 group. The feed conversion efficiency (FCR) was higher T2 and T3 groups than control group. From this study, it is concluded that silkworm pupa meal can be supplemented @ 3% level by replacing 5% protein supplements in grower crossbred pigs to improve growth, nutrient utilization, feed conversion efficiency and also to reduce the feed cost.